Power in sovereignty and its self-legitimation: on the autopoietic semantics and contingency of popular sovereignty. Issue 4 (2nd November 2015) - Přibáň, Jiří
Abstract: This paper analyses sovereignty as part of multiple power operations and the self-referential semantics of positive law and politics regarding the concept of popular sovereignty. The interplay between power structures and the self-description of society as democratic polity with popular sovereignty reflects on the typically modern tension between democracy as a contingent form of government and democracy as an imagined stable form of social totality. Using autopoietic social systems theory, the author reformulates the concept of sovereignty as the specific semantics internally constructed by the functionally differentiated systems of politics and law beyond the image of Leviathan and its socially integrating force, and independently of state organisation and its limitations.